Identifikasi Sektor Unggulan Kabupaten Bojonegoro Dan Strategi Pengembangannya - Trias Ayu Novitasari (Jurnal Administrasi Publik, 2014)
IDENTIFIKASI SEKTOR UNGGULAN KABUPATEN BOJONEGORO DAN STRATEGI PENGEMBANGANNYA Trias Ayu Novitasari, Heru Ribawanto, Abdullah Said Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, Malang E-mail: ctreazt@yahoo.com Abstract: Identification of Leading Sector of Kabupaten Bojonegoro and the Development Strategy. The identification of potential sector of Kabupaten Bojonegoro is needed to know because by that the government of Kabupaten Bojonegoro can manage and exploit the potential sector well to be developed to the maximum. Identification result of leading sector shows in Kabupaten Bojonegoro there are 4 leading sectors (agricultural sector, mining and quarrying, buildings, and services sector) and 5 non-leading sectors (industry and processing; electricity, gas, and clean water; trading, hotels, and restaurants; transport and communication; also financing sector, renting, and service company). Development strategy to the most potential sector is the mining and excavation particularly the oil and gas sub sector, the regional government does not have the authority to manage it so the regional government gives only strategy policy such as people empowerment. While the development strategy on agricultural sector particularly on rice commodity are by developing hybrid rice; assisting farmers through field schools; optimizing the using of Bengawan Solo water; optimizing the land use through movement of organic fertilizer use; garden movement using jajar legowo method; application of agricultural mechanization through the use of cropping tool or transplanter and harvesting tool such as powerthreser and combain harvester. Keywords: regional potency, leading sector, development strategy Abstrak: Identifikasi Sektor Unggulan Kabupaten Bojonegoro dan Strategi Pengemba-ngannya. Pengidentifikasian sektor unggulan Kabupaten Bojonegoro perlu untuk diketahui karena dengan diketahuinya sektor unggulan tersebut pemerintah Kabupaten Bojonegoro dapat mengelola dan memanfaatkan sebaik-baiknya sektor unggulan untuk dikembangkan secara maksimal. Hasil identifikasi sektor unggulan di Kabupaten Bojonegoro menunjukkan ada 4 sektor unggulan (sektor pertanian, pertambangan dan penggalian, bangunan, serta sektor jasa-jasa) dan 5 sektor bukan unggulan (sektor industri pengolahan; listrik, gas, dan air bersih; perdagangan, hotel, dan restoran; angkutan dan komunikasi; serta sektor keuangan, persewaan, dan jasa perusahaan). Strategi pengembangan untuk sektor paling unggul yaitu sektor pertambangan dan penggalian khusususnya subsektor migas, daerah tidak mendapatkan kewenangan untuk mengelola migas sehingga daerah hanya memberikan kebijakan strategi berupa pemberdayaan masyarakat. Sementara strategi pengembangan pada sektor pertanian khususnya komoditas padi adalah dengan pengembangan padi hibrida; pendampingan petani melalui sekolah lapang; optimalisasi kemanfaatan air bengawan solo; optimalisasi penggunaan lahan melalui gerakan penggunaan pupuk organik; gerakan taman dengan menggunakan metode jajar legowo; penerapan mekanisasi pertanian melalui penggunaan alat tanam atau transplanter dan alat panen yaitu powerthreser dan combain harvester. Kata kunci: potensi daerah, sektor unggulan, strategi pengembangan